Optimal serum cholesterol concentrations are associated with accelerated bone loss in African ancestry men. Issue 4 (April 2016) - Kuipers, A.; Miljkovic, I.; Evans, R.; Bunker, C.; Patrick, A.; Zmuda, J.
Abstract Summary We tested if serum lipid and lipoprotein cholesterol levels are associated with longitudinal measures of bone mineral density (BMD) in 1289 African ancestry men. After 6 years of mean follow-up, men with clinically optimal levels of low-density lipoprotein (LDL), high-density lipoprotein (HDL), or triglycerides at baseline experienced the greatest BMD loss, independent of potential confounding factors (allp  < 0.05). Introduction Studies of lipid and lipoprotein cholesterol associations with bone mineral density (BMD) and bone loss have been inconclusive, and longitudinal data are sparse. Therefore, the aim of this study was to test if fasting serum lipid and lipoprotein cholesterol levels are associated with areal and volumetric BMD and BMD change. Methods We determined the association of serum triglycerides, high-density lipoprotein (HDL), and low-density lipoprotein (LDL) cholesterol concentrations with cross-sectional and longitudinal (mean follow-up, 6.1 years) measures of BMD in a cohort of 1289 in African ancestry men (mean age, 56.4 years). Fasting serum triglycerides, HDL, and LDL were measured at baseline concurrent with BMD assessments. Dual-energy X-ray absorptiometry was used to quantify integral hip BMD, and peripheral quantitative computed tomography at the radius and tibia was used to quantify volumetric BMD. Men were categorized as optimal, borderline, or high risk for triglyceride, HDL, and LDL concentrations based on Adult Treatment Panel III guidelines. Results Lower serum triglyceride or LDL and higher HDL concentrations were associated with lower trabecular BMD at baseline (allp  < 0.05). Similarly, men classified as having optimal levels of LDL, HDL, or triglycerides at baseline experienced the greatest integral BMD loss at the hip and trabecular BMD loss at the tibia (allp  < 0.05), independent of potential confounding factors. Conclusions We found that clinically optimal serum lipid and lipoprotein cholesterol concentrations were associated with accelerated bone loss among Afro-Caribbean men. Further studies are needed to better understand the mechanisms involved and potential clinical significance of these findings.